Effect of Antimicrobial Activity 0f Starfruit Leaf Extract (Averrhoa bilimbi L.) on the Growth of Staphylococcus aureus Bacteria in Vitro - Efliani Efliani; Dwi Hilda Putri (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
This study aims to determine the effect of the antimicrobial activity of star fruit leaf extract on the growth of S.aureus bacteria. This study was conducted using the complete randomized design (RAL) method with 5 treatments and 3 repetitions. The treatment carried out is: the concentration of star fruit leaf extract is 10%, 20%, 30%, 40%, and 50%. The data obtained were analyzed using ANOVA with a confidence level of α= 0.05 and further tested with DNMRT. Antibacterial testing is carried out by the disc diffusion method to determine the formed inhibitory zone. The results showed the average diameter of the formation of the inhibitory zone at a concentration of 10% of 10.10 mm, 20% of 12.56 mm, 30% of 13.08 mm, 40% of 14.57 mm, and 50% of 15.97 mm. The optimum concentration of star fruit leaf extract in inhibiting the growth of S.aureus bacteria at a concentration of 50% is 15.97 mm. Key words: Staphylococcus aureus, antimicrobial, star fruit, inhibitory zone.